AN ANALYSIS OF AMY DUNNE'S PSYCHOPATH PROBLEM IN GONE GIRL MOVIE VIEWED FROM PSYCHOANALYSIS THEORY BY SIGMUND FREUD - Mukhammad Teguh Azisvirayuda; Teguh Kasprabowo (Universitas Stikubank (UNISBANK) Semarang, 2021)
The study aimed to analyze psychopathic problem of Amy Dunnes, the main character of Gone Girl movie, viewed from psychoanalysis theory by Freud. This study, employing qualitative method, explained the personalities of the main character in general and her psychopathic problem that she had. The dialogs and the scenes were analyzed to unfold the personalities and the psychopathic problems of the main character. The result showed that the main character had the following personalities: The main character wanted to have the perfect personality. Amy wanted to revenge when she was hurt, experiencing anxiety and being afraid of being punish, and Amy has paranoid thoughts about defeat.. The result also showed that the psychopathic problems of the main character were: Amy has a complicated behavior, Amy behaves manipulatively while planning revenge, Amy has a lack of empathy,Amy behaving sadistically to her husband, and Amy often lie to protect herself.